(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Reconfigurable sequential circuits find applications in various digital systems, including communication networks, data processing units, embedded systems, and FPGA-based designs. Their ability to adapt and reconfigure their functionality onthe-fly allows them to accommodate dynamic requirements and optimize the use of hardware resources. Traditional implementations of sequential circuits involve static configurations, where the logic and functionality are fixed during synthesis. While these methods are straightforward to design and implement, they lack adaptability and cannot be modified without redesigning the entire circuit. The proposed method involves the utilization of a dedicated Reconfigurable Logic Block (RLB) within the sequential circuits, allowing for dynamic configuration changes without altering the overall circuit structure. The RLB can be programmed to provide different logic functions using look up tables, multiplexers, enabling the sequential circuit such as counters and shift registers to change its behaviour.